2005
DOI: 10.1161/01.res.0000156891.66893.83
|View full text |Cite
|
Sign up to set email alerts
|

Action Potential Duration Restitution and Alternans in Rabbit Ventricular Myocytes

Abstract: Abstract-Action potential duration (APD) restitution properties and repolarization alternans are thought to be important arrhythmogenic factors. We investigated the role of intracellular calcium (Ca 2ϩ i ) cycling in regulating APD restitution slope and repolarization (APD) alternans in patch-clamped rabbit ventricular myocytes at 34 to 36°C, using the perforated or ruptured patch clamp techniques with Fura-2-AM to record Ca 2ϩ i . When APD restitution was measured by either the standard extrastimulus (S1S2) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
245
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(265 citation statements)
references
References 52 publications
15
245
5
Order By: Relevance
“…22 Also, depolarization-induced increase in intracellular Ca 2 + was inhibited by combined treatment with ryanodine and thapsigargin in rabbit ventricular myocytes. 23 Further, the finding showing that L-type Ca 2 + channel inhibitors suppress the ELT-induced positive inotropic effects indicates that Ca 2 + entry is also involved in this effect. Therefore, these results suggest that ELT increased atrial dynamics via activation of Ca 2 + entry through L-type Ca 2 + channels and Ca 2 + release from the SR (Fig.…”
Section: Figmentioning
confidence: 97%
See 1 more Smart Citation
“…22 Also, depolarization-induced increase in intracellular Ca 2 + was inhibited by combined treatment with ryanodine and thapsigargin in rabbit ventricular myocytes. 23 Further, the finding showing that L-type Ca 2 + channel inhibitors suppress the ELT-induced positive inotropic effects indicates that Ca 2 + entry is also involved in this effect. Therefore, these results suggest that ELT increased atrial dynamics via activation of Ca 2 + entry through L-type Ca 2 + channels and Ca 2 + release from the SR (Fig.…”
Section: Figmentioning
confidence: 97%
“…Combined treatment with ryanodine and thapsigargin fully suppresses SR Ca 2 + cycling and elevation of intracellular Ca 2 + induced by stimulation in canine sinoatrial node and rabbit ventricular myocytes. 22,23 It has been known that the combined treatment with ryanodine and thapsigargin inhibits isoproterenol-induced increase in intracellular Ca 2 + levels in the Langendorff-perfused canine sinoatrial node. 22 Also, depolarization-induced increase in intracellular Ca 2 + was inhibited by combined treatment with ryanodine and thapsigargin in rabbit ventricular myocytes.…”
Section: Figmentioning
confidence: 99%
“…This is known as the restitution hypothesis [228]. However, there is contradictory evidence regarding its validity [229,230]. In effect, various authors reported severe shortcomings of the mentioned criteria [231,232].…”
Section: Dynamicsmentioning
confidence: 99%
“…Representative I Na traces (no. 1,10,15,20,25) elicited by the test pulse are illustrated in Fig. 3B and reflects this depolarizing shift in half-inactivation (increased I Na availability) for TS-NS/LQT3 cells since peak I Na at trace 1 and 10 are comparable in amplitude.…”
Section: Gating Defects Of N 1325 S Sodium Channels In Ventricular Cellsmentioning
confidence: 78%
“…3,Table 1) led us to speculate that the generation and/or maintenance of AP prolongation were largely due to some instability in [Ca 2+ ] i ions. Beat-to-beat variability of repolarization and abnormalities in [Ca 2+ ] i in cardiomyocytes has been recognized [13][14][15][16]. As shown in Fig.…”
Section: Action Potential Alternans and The Effects Of Verapamilmentioning
confidence: 97%